PENGARUH ATRIBUT - ATRIBUT PRODUK YAMAHA JUPITER-Z TERHADAP KEPUASAN KONSUMEN (SUATU SURVEI PADA DEALER MEGA UTAMA MOTOR DI JAKARTA BARAT) - Rizki Ahmad Fauzi; Siana Ria (Jurnal Ilmiah Binaniaga, 2006)
The growth of worldwide automotive industrial sector forced PT Yamaha, as a Japanese motorcycle (known as Yamaha) producer, to enter the motorcycle market in Indonesia. Yamaha has grown and developed rapidly and has been successfully placed it self in the second rank that dominated about 25% of the motorcycle market share. PT Yamaha tries to understand the customer characteristics that are not dependant of interest and demand, but also to create product innovation through research and development product program. The writer is interested in Jupiter Z product and did a research to find out the correlation between Jupiter Z attributes with consumer’s satisfaction. The research used quantitative descriptive method and a survey carried out at Mega Motor in West Jakarta. The research compared two variables of attribute including physical performance, color variance, engine performance, safety and easy handle, engine maintenance, guarantee and claim, fuel consumption, spare parts supply, after sales service and resale value. There were 100 respondents involved in the survey, the writer used Likert Scale of 1 – 5 with the aggregate variables that were plotted in Cartesian diagram using performance importance analysis. The results were between 3.33 – 3.98 with average value of 3.78 (quite satisfied) and importance attribute ranged from 3.98 – 4.31 with average value of 4.16 (important). From the Cartesian Diagram we can see that in Quadrant I (top priority) the respondents concern about guarantee, claim and after sale service while Quadrant II (dependent priority) the respondents thought about physical performance, engine performance, security and easy to drive, engine maintenance, supplies and spare parts. In the third Quadrant (low priority) respondents considered fuel consumption and resale value while in the last Quadrant (over priority) respondents chose color variance. Kata